Transforming adaptive management in knowledge-intensive enterprises - A. A. Sazonov; M. V. Sazonova (Управление)
The article considers the aspects of transforming the adaptive management of knowledge-intensive enterprises under highly volatile institutional conditions in the current technological order. The initial scientific hypothesis was that the quality and efficiency of enterprises in the medium and long term is a consequence of management system transformation, as a result of using a wide range of digital technologies in the process of implementating preventive management measures aimed at maintaining a certain level of correspondence between the digital environment and the internal capacity of the management system.The structural aspects of the concept of adaptive transformation of the management system of knowledge-intensive enterprises in a highly variable digital environment have been analysed. An algorithm that represents a complete independent system has been proposed in which the order and levels of interconnection between individual subsystems and elements have been determined, with the adaptive transformation process itself as the central link, which is supported by a complex of different subsystems. A methodological approach for implementating a multicomponent process of adaptive management system development has been presented, detailing the various methodological recommendations and developments. The methodological techniques used for the indicative assessment of the level of efficiency of the management system of knowledge-intensive enterprises have been outlined.An independent and unified digital management environment for knowledge-intensive enterprises enables real-time analysis of business processes in order to make timely, high-quality and effective decisions in the following key areas: investment and financial activities; enterprise knowledge and personnel management; production and technical management; logistics, operations and disposal. The article offers methodological recommendations on the reengineering of business processes in knowledge-intensive enterprises in a new technological mode.